Clinical outcome of laninamivir octanoate hydrate for influenza in the 2013–2014 Japanese season. Issue 11 (November 2015) - Ikematsu, Hideyuki; Kawai, Naoki; Iwaki, Norio; Kashiwagi, Seizaburo
Abstract The clinical outcome of laninamivir octanoate hydrate (laninamivir) in the Japanese 2013–2014 influenza season was investigated. A total of 235 patients were enrolled, of whom 222 were evaluated for the duration of fever and other symptoms. The types/subtypes were 101 A(H1N1)pdm09 (45.5%), 37 A(H3N2) (16.7%), and 84 B (37.8%). The median durations of fever were 32.0, 41.0, and 50.0 h, and the median durations of symptoms were 74.5, 85.0, and 95.0 h for A(H1N1)pdm09, A(H3N2), and B, respectively. The differences among the three groups were not statistically significant. There was no significant difference in the duration of fever or symptoms between patients under 10 and 10 years or over. The median durations of fever were 46.0 and 58.0 h and the median durations of symptoms were 95.0 and 77.0 h for the Yamagata and Victoria lineages, respectively. The virus positive rates at day 5 were significantly different at 31.5% (28/89), 12.1% (4/33), and 34.7% (26/75) for the three type/subtypes, respectively. The virus positive rates for A(H1N1)pdm09 and B were significantly higher for the patients under 10 years than for the patients 10 years or older. (p = 0.0379 and 0.0320, respectively). No significant increase was found between the IC50 of days 1 and 5. No adverse drug reactions associated with laninamivir were reported. These results indicate the continuing clinical utility of laninamivir against influenza, irrespective of the virus type/subtype or lineage, and that it is unlikely that the clinical use of laninamivir will lead to selection of resistant virus.